Bede, iconoclasm and the Temple of Solomon. Issue 4 (10th October 2013) - Darby, Peter
<x xml:space="preserve">Abstract</x> In Bede's lifetime (c.673–735) the churches at Wearmouth‐Jarrow were richly decorated with panel paintings from Rome. This essay examines the significance that those paintings held for Bede and his community, and it reveals the strategies that Bede employed to defend them in his commentary on the Temple of Solomon (De templo), which was written after images had become a contentious issue in Byzantium during the reign of Emperor Leo III (714–41). This has important implications for our understanding of Bede's place in the intellectual landscape of early eighth‐century Europe, and it shows the ambitious nature and topical relevance of his mature exegetical programme.